The Independence of the Tax Court within Indonesia’s Judicial Power System - I Wayan Kandia; I Wayan Eka Santika; Putu Windu Mertha Sujana (CV. Tirta Pustaka Press, 2026)
This study examines the unresolved constitutional inconsistency surrounding the institutional position of the Indonesian Tax Court, particularly the dualism of judicial and executive supervision that continues to challenge judicial independence. The Tax Court plays a strategic role in resolving tax disputes between taxpayers and the government; however, its institutional position remains controversial due to the dualism of administrative and judicial supervision. This research applies a normative legal method through statutory, conceptual, and comparative approaches to critically evaluate whether the Tax Court’s institutional structure complies with constitutional principles of judicial independence and separation of powers. The study finds that the continued administrative and financial control exercised by the Ministry of Finance creates structural conflicts of interest that weaken the institutional impartiality of the Tax Court and contradict constitutional guarantees of judicial independence. This institutional dependency risks weakening taxpayer confidence in judicial neutrality, reducing legal certainty, and undermining the legitimacy and fairness of Indonesia’s tax dispute resolution system. This study argues that strengthening the institutional independence of the Tax Court is essential to ensure an impartial judiciary and to uphold the principles of the rule of law. The study recommends comprehensive legislative reform and the full integration of the Tax Court into the Supreme Court’s one-roof judicial system to ensure institutional independence and constitutional conformity.